Interaction Between microRNAs and Myeloid-Derived Suppressor Cells in Tumor Microenvironment - Liang, Lifei; Xu, Xiaoqing; Li, Jiawei; Yang, Cheng (Frontiers in Immunology, 2022)
Myeloid-derived suppressor cells (MDSCs) are a heterogeneous population of cells generated during a series of pathologic conditions including cancer. MicroRNA (miRNA) has been considered as a regulator in different tumor microenvironment. Recent studies have begun to unravel the crosstalk between miRNAs and MDSCs. Knowledge of the effect of both miRNAs and MDSCs in tumor may improve our understanding of the tumor immune escape and metastasis. The miRNAs target cellular signal pathways to promote or inhibit the function of MDSCs. On the other hand, MDSCs transfer bioinformation through exosomes containing miRNAs. In this review, we summarized and discussed the bi-directional regulation between miRNAs and MDSCs in tumor microenvironment.